Maximum Bridging Suture Tension Provides Better Clinical Outcomes in Transosseous-Equivalent Rotator Cuff Repair: A Clinical, Prospective Randomized Comparative Study. Issue 9 (July 2020) - Oh, Joo Han; Park, Ji Soon; Rhee, Sung-Min; Park, Joo Hyun
Background: Some studies reporting clinical outcomes after transosseous-equivalent (TOE) repair have attributed type II rotator cuff failure to excessive bridging suture tension, as it can cause overloading on the medial row. In a previous biomechanical cadaveric study, increasing bridging suture tension over 90 N did not improve the contact area and ultimate failure load of the TOE construct, despite increasing the contact force and contact pressure. Purpose: To compare the clinical outcomes of different bridging suture tensions after TOE rotator cuff repair based on the results of a previous biomechanical study. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: A total of 78 patients who underwent arthroscopic rotator cuff repair for medium- to large-sized tears were prospectively enrolled and randomly divided into 2 groups according to the applied bridging suture tension: optimum tension group (96.3 ± 4.9 N) and maximum tension group (199.0 ± 20.3 N). Bridging suture tension was measured with a customized tensiometer, as used in the previous biomechanical study. The functional outcome was measured at the final follow-up (27.4 ± 5.9 months [range, 24-45 months]) using the visual analog scale for pain, American Shoulder and Elbow Surgeons score, Simple Shoulder Test, and Constant score, and the anatomic outcome was evaluated using magnetic resonance imaging or ultrasonography at least 12 months after surgery. Results: Overall, 64 patients (32 in each group) were analyzed. The functional outcomes improved significantly compared with preoperative values (all P < .05) but did not show significant differences between the 2 groups (all P > .05). Regarding the anatomic outcomes, the maximum tension group (n = 1; 3.1%) had a significantly lower healing failure rate than the optimum tension group (n = 9; 28.1%) ( P = .013). One patient in the maximum tension group had a type II failure. Conclusion: Maximum bridging suture tension in TOE repair for medium- to large-sized rotator cuff tears provided better anatomic healing with less risk of medial rotator cuff failure, which differs from the results of a previous time-zero biomechanical study.